Age-stratified treatment variations in acute intracranial surgery for traumatic brain injury in Europe: a prospective observational study within CENTER-TBI - Vreeburg, Rick J. G.; Singh, Ranjit D.; van Dijck, Jeroen T.J.M.; den Boogert, Hugo F.; Yue, John K.; Lagares, Alfonso; Depreitere, Bart; Moojen, Wouter A.; Younsi, Alexander; van Erp, Inge A.M.; de Ruiter, Godard C.W.; Maas, Andrew I.R.; et al. (Journal of neurotrauma, 2026)
High-quality evidence to guide the practice of acute cranial surgery across age groups in traumatic brain injury (TBI) remains sparse. Current surgical guidelines generally do not consider age in their recommendations. The aim of the study is to evaluate acute cranial surgery rates and center treatment differences across age in TBI. Data were extracted from the prospective observational Collaborative European NeuroTrauma Effectiveness Research in TBI (CENTER-TBI) study. The CENTER-TBI study included patients with TBI between 2014 and 2017 from 65 level 1 trauma centers across Europe and Israel. Data from all 27,358 patients with TBI enrolled in the CENTER-TBI core study (n = 4509) and registry (n = 22,849) were considered. Eight patients with missing age were excluded, leading to a final analytic sample of 27,350 (core study n = 4504, registry n = 22,846). Variations in probability, defined as case-mix adjusted proportions, of acute surgical treatment of intracranial mass effect (primary decompressive craniectomy or craniotomy), performed within 24 h of initial injury, were expressed using median odds ratios (MORs). Adjusted odds ratios (aORs) were calculated using random-effects linear regression to assess the association between age and the probability of acute cranial surgery for acute subdural hematoma, epidural hematoma, or intracerebral hemorrhage/contusions. MORs and aORs were reported with 95% confidence interval (CI). The odds of acute surgery decreased with older age (aOR = 0.93, 95% CI: 0.92-0.95, per each interquartile range increase of 37 years [y]). Variations in center-specific surgery rates increased with age (15-24 y: MOR = 1.4; 25-44 y: MOR = 1.5; 45-64 y: MOR = 1.6; 65-79 y: MOR = 1.8; ≥80 y: MOR = 3.3), except for patients aged <15 y (MOR = 2.9). Older patients with TBI were less likely to receive acute cranial evacuation surgery, independent from other (comorbidity) factors. Higher age was associated with more surgical treatment variation between centers. Neurosurgery for TBI can be improved by age-personalized treatment algorithms.
Gesehen am 17.02.2026